Proses pemanfaatan modul bonggol jagung berbentuk balok menjadi material utama desain lampu - Muhamad Ediyansyah; Andry Masri (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
The result of the exploration of corncob is a module in the form of a block at this stage of the corncob research with this form will be used as the main component of the product, this research was conducted with a material exploration approach, to explore the potential material of corncob which is expected to be a product that has novelty value. so an experiment is needed on corncobs. The experiments carried out were (1) the development of the physical treatment of the previous square module which had been explored by the industry to find the potential contained in the corncob. (2) Experiment with the corncob square module by using assembly methods and techniques in order to obtain new shapes and potentials. The research was conducted to obtain a product design with an emphasis on material aspects in order to obtain the characteristics of the corncob material. This research provides new opportunities and hopes for the community to have new creations in utilizing the corncob module.